Assessment of diet-related changes on albendazole absorption, systemic exposure, and pattern of urinary excretion in treated human volunteers - Ceballos, Laura (2021)
Soil-transmitted-helminth (STH) infections are a persistent global public health problem. Control strategies for STH have been based on the use of mass drug administration (MDA) mainly targeting preschool- and school-aged-children, although there is increasing interest in expanding treatment to include adults and others through community-wide MDA. Coverage assessment is critical to understanding the real effectiveness of albendazole (ALB) treatment in those MDA programs. The work described here aims to (i) evaluate the effect of type of diet (a heavy or light meal) and fasting before ALB treatment on the systemic disposition of ALB and its metabolites in treated human volunteers and (ii) evaluate the potential feasibility of detecting albendazole metabolites in urine. The data reported here demonstrate that the systemic availability of the active ALB-sulfoxide (ALBSO) metabolite was enhanced more than 2-fold after food ingestion (a heavy or light meal). ALB dissolution improvement related to the ingestion of food may modify the amount of drug/ metabolites reaching the parasite, affecting drug efficacy and the overall success of MDA strategies. The measurement in urine samples of the amino-ALB-sulfone (NHALBSO2) derivative and ALBSO for up to 96 h suggests that it may be feasible to develop a noninvasive tool to evaluate compliance/adherence to ALB treatment.